Executive Director’s Message - Harley, Catherine (Operating Room Nurses Association of Canada Journal, 2015)
It has been a privilege to serve as your Executive Director for the last five years and it is with a high level of respect that I stepped down from this position in July. This was not an easy decision as my time in this role has been very rewarding. That is, in no small part, thanks to all of you - the dedicated and hard-working perioperative registered nurses that make up the heart and soul of ORNAC. While there is still work ahead (and there always will be as a strong association must continue to grow and expand) I am confident that I have left ORNAC well-positioned for the future and ready to fulfill its responsibilities to the Canadian public with great success.